2020
DOI: 10.1038/s41598-020-62720-6
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nutritional Risk Index (GNRI) and Creatinine Index Equally Predict the Risk of Mortality in Hemodialysis Patients: J-DOPPS

Abstract: the geriatric nutritional risk index (GnRi) and creatinine (cr) index are indexes often used as nutritional surrogates in patients receiving hemodialysis. However, few studies have directly compared the clinical characteristics of these two indexes. We investigated 3,536 hemodialysis patients enrolled in the Japan DOPPS phases 4 and 5. The primary outcome was all-cause mortality and the main exposures were the GNRI and Cr index. We confirmed and compared the association between these indexes and mortality risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 31 publications
(24 reference statements)
3
68
0
1
Order By: Relevance
“…Tsai et al 32 recently reported that SCI was an independent predictor of the presence of protein energy wasting. Moreover, Yamada et al 33 demonstrated that GNRI and SCI equally predicted all-cause mortality in hemodialysis patients. In the present study, CT-measured PMTH was independently and positively associated with both SCI and GNRI, suggesting that PMTH may be an indicator of protein energy wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Tsai et al 32 recently reported that SCI was an independent predictor of the presence of protein energy wasting. Moreover, Yamada et al 33 demonstrated that GNRI and SCI equally predicted all-cause mortality in hemodialysis patients. In the present study, CT-measured PMTH was independently and positively associated with both SCI and GNRI, suggesting that PMTH may be an indicator of protein energy wasting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GNRI, a relevant marker for nutrition and mortality, is defined via serum albumin in addition to body weight, which is mainly determined by muscle content. We examined the importance of the creatinine index, another nutritional marker in HD patients without residual renal function, as a predictor of mortality risk [ 29 ]. The creatinine index is calculated using the following formula: Cr index = 16.21 ( +1.12 if male) − 0.06 × [age (years] − 0.08 × (single pool Kt/V) + 0.009 × [serum creatinine (μmol/L].…”
Section: Significance Of Sarcopenia In Relation To Harmful Effects Of Malnutrition In Hd Patientsmentioning
confidence: 99%
“…Thus, the creatinine index is a nutritional marker that is mainly determined in HD patients by muscle content, given the lack of apparent residual renal function. We found that lower GNRI and Cr index values were both independently and equally associated with an increased risk of all-cause mortality in a multivariable-adjusted model [ 29 ]. Taken together, these findings demonstrate that the mechanism by which malnutrition increases mortality risk in Japanese HD patients can be mostly explained by reduced muscle mass.…”
Section: Significance Of Sarcopenia In Relation To Harmful Effects Of Malnutrition In Hd Patientsmentioning
confidence: 99%
“…Two radiologists separately scored and averaged. The calculation of geriatric nutrition risk index (GNRI) [ 19 ] can be estimate by …”
Section: Methodsmentioning
confidence: 99%